DO FINTECH ADOPTION AND FINANCIAL PERFORMANCE AFFECT ISLAMIC BANK MARKET SHARE? A FEM APPROACH - Wirdyansyah, Danial Muhammad; Azzahra, Shafira Apriliesya; Ramadhani, Rahma Nazila (Universitas Suryakancana, 2025)
This study explores the impact of fintech adoption on the market share of seven Islamic Commercial Banks (BUS) over a three-year observation period (2021-2023). Using a quantitative approach based on the Fixed Effect Model (FEM) and panel data from financial statements, the results show that fintech adoption has a positive and significant effect on market share, with a p-value of 0.000. Services such as mobile banking, digital payment systems, and online financing platforms contribute to increasing the accessibility of Islamic financial services and strengthening financial inclusion. Emerging markets show rapid expansion of fintech, making digital transformation a key factor in improving the competitiveness of Islamic banking. Therefore, regulations are needed that support fintech innovation while ensuring compliance with Shariah principles. In addition, strengthening cybersecurity, improving user experience, and integrating artificial intelligence-based financial solutions can further increase the market share of Islamic banking. The findings provide insights for Islamic banks in developing fintech-based business strategies, as well as a basis for further research to examine the long-term sustainability of fintech adoption in the Islamic banking ecosystem